Spatial Distribution of Some Toxic Metals in Topsoil and Bioaccumulation in Wild Flora Around a Metal Scrap Factory A Case of Southwestern Nigeria - Ogunkunle, Clement O. (Journal of Environmental Science and Management, 2017)
There is increasing metal pollution in soil due to the spate of industrialization in developing countries. It is premised on this scenario that the topsoil around a metal scrap factory was studied to assess the spatial distribution of metal and resultant mobility in native flora. Concentrations of Cd, Zn, Pb and Fe in samples of topsoil and plants were determined by Atomic Absorption Spectrophotometry. Spatial modelling of metals was carried out using the Inverse Distance Weighted (IDW) technique of ArcGIS. Also, metal mobility in native flora was assessed by the transfer factor model. The analysis showed high levels of Cd, Zn, Fe and Pb that were beyond natural concentrations. Spatial mapping of the concentrations indicated that the immediate north and south of the factory were significantly polluted by Cd, Zn and Pb while Fe presence in the area was partially geogenic. The level of Cd, Zn and Pb in the three native species exceeded permissible limits whereas only Cd showed great mobility within the biomass of the three species. The mobility of Cd in the diagnostic species is an indication of possible potential health risk from Cd toxicity through plants ingestion. It is therefore important that measures should be geared towards improving the pollution control system of the factory to stem down the rate of contamination of soil.